The Effect of Local Original Income, Regional Levies and Regional Tax Contributions on Regional Expenditures of Brebes Regency for the 2017-2021 Period - Azizah, Silvia Syarifatul; Wulandari, Hilda Kumala; Dumadi, Dumadi (Journal Of Accounting Management Business And International Research, 2022)
This study aims to identify and evaluate the effect of local taxes, expenditures, and revenues on local expenditures. In 2017–2021, at the BAPPEDA and BPKAD offices in Brebes Regency. Quantitative in nature, this type of research uses secondary data. The main focus of this research is the implementation of the Regional Budget of Brebes Regency for one month because of the targeted use of skewers in the sewing stitch research. Usage is made of secondary data. then tested, including research hypotheses, multiple linear regression analysis, traditional hypothesis testing, and descriptive statistical analysis tests. SPSS Version 25 program was used to perform the test. The findings of this study indicate that this occurs as a result of the tests carried out: 1) local revenue has a positive and significant effect on regional spending, 2) regional retributions have a significant and positive effect on regional expenditures, 3) the contribution of local taxes is positive and significant on regional spending. and 4) local revenue, regional levies, local tax contributions have a significant simultaneous effect on regional spending.